2013
DOI: 10.1111/ele.12083
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of plant lineages shapes herbivore phylogenetic beta diversity along ecological gradients

Abstract: Understanding drivers of biodiversity patterns is of prime importance in this era of severe environmental crisis. More diverse plant communities have been postulated to represent a larger functional trait-space, more likely to sustain a diverse assembly of herbivore species. Here, we expand this hypothesis to integrate environmental, functional and phylogenetic variation of plant communities as factors explaining the diversity of lepidopteran assemblages along elevation gradients in the Swiss Western Alps. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
130
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(139 citation statements)
references
References 55 publications
9
130
0
Order By: Relevance
“…Our multivariate analyses demonstrated relationships between fungal assemblages and environmental conditions that were similar to those classically observed for macroorganisms (48,54,55). Our results demonstrated that fungal diversity in the aerosols generated during this activity is quite homogenous in fungal composition in spite of geographic distance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our multivariate analyses demonstrated relationships between fungal assemblages and environmental conditions that were similar to those classically observed for macroorganisms (48,54,55). Our results demonstrated that fungal diversity in the aerosols generated during this activity is quite homogenous in fungal composition in spite of geographic distance.…”
Section: Discussionsupporting
confidence: 83%
“…To determine the fungal phylogenetic beta diversity, the mean pairwise distance was calculated using the comdist function in the Picante, version 1.6, package (43). The standardized effect size of the mean phylogenetic distance across communities was computed in the same way used for the NRI by calculating a standardized effect size, as described by Swenson (47) and Pellissier et al (48). Finally, the two beta diversities, taxonomic and phylogenetic, were correlated with the variation in abiotic and biotic variables and with the differences in farming systems ( Table 2).…”
Section: Figmentioning
confidence: 99%
“…Plants support a wide array of herbivore species. In turn, herbivores feed on groups of closely related genera or plant species [6971]. Thus, changes in plant assemblages may cause changes in composition of insect assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Dinnage et al (33), for example, found that more phylogenetically diverse plant communities (a potential proxy for communities with more diverse defensive and nondefensive traits) had a strong positive influence on the species richness of herbivorous insects in Minnesota. Similarly, Pellissier et al (34) provided evidence that plant phylogenetic diversity correlated with diversity of lepidopteran assemblages in the Swiss Western Alps. As more plant communities are studied in the future it will be interesting to see whether dissimilarity of nonresistance plant traits can also contribute to increased herbivore specialization.…”
Section: Discussionmentioning
confidence: 93%